The 'collapse' of the Fifth WTO Ministerial Conference : a preliminary assessment - Bardouille, Nand C. (2003)
Explores the issues that were differences between WTO members. Looks at the nature of the Caribbean's preparations leading up to and at Cancún. Assesses the road-map for the multilateral trading system in the aftermath of the failed Ministerial.